2020
DOI: 10.1177/1073858420939552
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Motor Learning Processes in Humans: Defining Their Neurophysiological Bases

Abstract: Learning new motor behaviors or adjusting previously learned actions to account for dynamic changes in our environment requires the operation of multiple distinct motor learning processes, which rely on different neuronal substrates. For instance, humans are capable of acquiring new motor patterns via the formation of internal model representations of the movement dynamics and through positive reinforcement. In this review, we will discuss how changes in human physiological markers, assessed with noninvasive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 155 publications
(230 reference statements)
3
66
0
2
Order By: Relevance
“…3 ), it is possible that instructive and reinforcement motor learning are more heavily engaged in the initial, cognitive stage of learning when performance is variable and the learner has to explore different movement solutions, whereas the associative stage engages primarily reinforcement and use-dependent mechanisms as the learner continues to refine their behavior with extensive practice. In the autonomous stage, further adjustments to motor behavior and a shift to automaticity may primarily be driven by sensorimotor adaptation and continued movement practice (similar to that suggested by the authors of previous reviews 21 , 40 ). This working theory aligns with Gentile’s description of explicit and implicit processes that contribute to motor skill acquisition.…”
Section: Future Research Directionsmentioning
confidence: 53%
See 2 more Smart Citations
“…3 ), it is possible that instructive and reinforcement motor learning are more heavily engaged in the initial, cognitive stage of learning when performance is variable and the learner has to explore different movement solutions, whereas the associative stage engages primarily reinforcement and use-dependent mechanisms as the learner continues to refine their behavior with extensive practice. In the autonomous stage, further adjustments to motor behavior and a shift to automaticity may primarily be driven by sensorimotor adaptation and continued movement practice (similar to that suggested by the authors of previous reviews 21 , 40 ). This working theory aligns with Gentile’s description of explicit and implicit processes that contribute to motor skill acquisition.…”
Section: Future Research Directionsmentioning
confidence: 53%
“…Rather, there are multiple mechanisms of motor learning that can occur in parallel or in isolation to ultimately lead to sustained changes in motor behaviors. 19 , 21 In this section, we provide an overview of 4 widely studied motor learning mechanisms: use-dependent, instructive, reinforcement, and sensorimotor adaptation-based motor learning. We will describe the key features of these mechanisms including the primary behavioral drivers, neural substrates, cognitive involvement, and timescales.…”
Section: Four Mechanisms Of Motor Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than affecting motor adaptation solely via a cerebellar-motor circuit, a plausible alternative suggestion is that the effect of cerebellar stimulation may result from modulation of the cerebellar-cognitive network (i.e. through modifying explicit mechanisms such as the use of strategies [16]), or an interplay between both circuits (see also [17]). This could potentially explain the difficulties seen in studies attempting to separately modulate the implicit and explicit components of motor adaptation [18], and could plausibly explain the results of work reporting effects of cerebellar stimulation on motor savings [13], as recent research suggests savings may be linked to explicit learning mechanisms [19].…”
mentioning
confidence: 99%
“…Previous studies demonstrated that motor skill learning relies on several processes such as use-dependent plasticity, reinforcement, and error-based learning 15 , 16 . In addition, the contribution of each of these processes varies with learning phase (i.e., early or late phase) 17 . Therefore, some previous neuroimaging studies adopted a several-weeks practice schedule to clarify time-dependent acquisition of memory representation of motor skill components 18 20 .…”
Section: Introductionmentioning
confidence: 99%